Analisis Isi Lambung Ikan Senangin (Eleutheronema tetradactylum Shaw) di Perairan Dumai - Titrawani Titrawani; Roza Elvyra; Ririk Ulfitri Sawalia (Al-Kauniyah: Jurnal Biologi, 2013)
The research about stomach content analysis of thraedfin fish (Eleutheronema tetradactylum Shaw) “senangin fish” in Dumai aquatic was taken out on July until Maret 2011. The research aimed to know the kind of senangin fish’s food include main food, supplement food and additional food. The used analysis based on Natarjan and Jingran in Effendi (1979), by analysis index of preponderance (Higher Part Index). Based on them main food of senangin fish are  Crustacea,  Engraulidae and animal debric.